Reconceptualizing Curriculum Integration through the Islamization of Knowledge in Islamic Secondary Education - Fitria, Rani; Afrinila, Afrinila; Rismanilda, Rismanilda; Revalina, Yeni; Lahmi, Ahmad (Ahlussunnah: Journal of Islamic Education, 2026)
Epistemological dualism separating general (kauniyah) and religious (qauliyah) knowledge remains an intellectual barrier to the advancement of Islamic education. This study aims to deconstruct and analyze the application of the Islamization of Knowledge as a philosophical foundation for curriculum integration in Islamic secondary education. This research employs a qualitative method with a content analysis approach to examine and synthesize the perspectives of Ismail Raji al-Faruqi and Syed Muhammad Naquib al-Attas within the context of contemporary curriculum models. The findings reveal that curriculum integration cannot be implemented through an additive approach, such as merely attaching religious texts to scientific subjects. Instead, it requires a reconstruction of the hierarchy of knowledge that places tawhid as the central epistemological foundation. At the practical level, this integration can be operationalized through the adoption of integrated and webbed curriculum models, as well as the “Spider Web” paradigm, which facilitates an interconnected dialogue between sacred texts and empirical realities. Furthermore, within the framework of the Merdeka Curriculum, this integration aligns with the Project for Strengthening the Pancasila Student Profile, enabling the internalization of Islamic values through a transdisciplinary approach to develop adaptive learners in the era of Society 5.0. Theoretically, this study affirms that the Islamization of Knowledge in curriculum design is a conditio sine qua non for nurturing ulul albab generations characterized by intellectual competence and spiritual integrity.